Perbedaan Pengaruh Open Kinetic chain dan Close Kinetik Chain Dengan Kombinasi TENS Terhadap Kemampuan Fungsional Pada Penderita Ostheoarthritis Knee - Siti Kholifah; Rachma Putri Kasimbara; Ahmad Abdullah; Yohanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Osteoarthritis knee is one of the most common musculoskeletal disorders and is caused by degenerative factors. Osteoarthritis of the knee is the cause of the dysfunction. People with knee osteoarthritis commonly complain of pain, stiffness, and dysfunction. Motor chain tension and motor chain proximity to improve functionality in patients with osteoarthritis knee.Methods: This research is a quasi-experimental research. The study design, on the other hand, used a pre-test and post-test group design. Two treatment groups were used in this study. That is, treatment group 1: TENS and open kinetic chain up to 8 people, treatment group 2: TENS and closed kinetic chain up to 8 people. Both groups of samples were measured for functionality using WOMAC. Frequency of exercise 3 times a week for 4 weeks.Results: Data collection was carried out using the WOMAC index. The data collected were tested for normality using the Shapiro Wilk method & analyzed using an independent t-test.Conclusion: Differences in the effect of open and closed kinetic chains on TENS on functional improvement in patients with knee osteoarthritis.